Pengelolaan Excellent Service di Sekolah Menengah Kejuruan - Sulistianto, Heri (Universitas Muhammadiyah Surakarta, 2017)
The purposes of conducting this study are : (1) Identifiying how to plan the excellentservice in SMK Negeri 2 Wonogiri. (2) Identifiying the implementation of excellentservice in SMK Negeri 2 Wonogiri. (3) Identifiying the evaluation of excellent serviceimplementation in SMK Negeri 2 Wonogiri. The techniques of collecting data applywith a depth interviews, observations and documentations. The dataanalysis usesdescreptive-quality analysis model. The resultsof the study are : (1) the excellentservice in SMK Negeri 2 Wonogiri is conducted by a good planning and regulary.The excellent service planning is adjusted to the priority on the quality objectives setby the princopal that has been designed by each line of work, then formulated theplanning in order to APBS adjusted to the conditions how can improve the excellentservice. (2) The implementation of excellent service in SMK Negeri 2 Wonogiri in thefield of curiculum according to the latest government regulations and conducted wellwill make the learning process more effectively and efficiently, in the field of studentaffairs, the enactment and enforcement dicipline for students are done gradually andcountinously, also the choice of extracurricular activities are implemented to channelthe talents and interests of learners outside school hours, in the field of facilities andinfrastructure, it always completes the building and educational facilities continually.In the field of public relations that is by estabilishing communication with theindustrial world as much as possible so that it can be used for job training process,work apprenticeship as well as presenting guest teacher, in the field of administrationis the establisment of documentations and service system for the tecaher and learners.(3) Evaluation is carried out periodically,weekly, monthly, every quarter of everysemester or the end of the school year, the process is adapted to the field conditions.A thorough evaluation of the implementation of excellent service at SMK Negeri2 Wonogiri is conducted in management review activities annualy as part of theISO 9001 : 2008 quality management system proces in which there are inputs fromcostumers that effect the improvement of school services greatly.